Habitat associations of woody plant species in evergreen–deciduous broadleaf karst forests in southwest China - Su, Liang; Du, Hu; Zeng, Fuping; Wang, Hua; Lu, Menzhen; Luo, Liujuan; Peng, Wanxia; Song, Tongqing (Frontiers in Ecology and Evolution, 2023)
The effects of habitat filtering on community assembly have been extensively researched, and topography has been identified as a critical factor influencing the spatial distribution of trees. In this study, we established a 25-ha plot in karst evergreen-deciduous broadleaf forests in southwestern China. Eight topographical factors were used to divide plots into four habitat types, i.e., hilltop, steep slope, gentle slope and depression, using a multivariate regression tree. A total of 85 evergreen and deciduous tree species were recorded in these four habitats and classified into three life stages, the differentiation of which was assessed using torus-translation tests. We identified 65 significant positive habitat associations and 79 significant negative associations. Most species, whether evergreen or deciduous, exhibited a positive correlation with steep slopes, whereas relatively few species were adapted to depressions. Moreover, the percentage of evergreen species positively associated with hilltops and steep slopes was higher than that of deciduous species. Both evergreen and deciduous species showed an increasing percentage of positive correlation with hilltops from sapling stage to mature stages. However, more evergreen species grew on steep slopes in the sapling stage, whereas deciduous species are mature stage. We used canonical correspondence to analysis the relationship between species and the eight topographical factors. Regardless of life form or life stage, results showed that species distribution was significantly affected by topography. Furthermore, the distribution of evergreen species on sapling stage trees was found to be higher influenced by topography, whereas deciduous species was higher influenced by topography on mature stage. Finally, we identified elevation as the most crucial topographical factor affecting species distribution.